Sleep Quality and Daytime Sleepiness Among Women With Urgency Predominant Urinary Incontinence. Issue 2 (March 2018) - Winkelman, William D.; Warsi, Ann; Huang, Alison J.; Schembri, Michael; Rogers, Rebecca G.; Richter, Holly E.; Myers, Deborah L.; Kraus, Stephen R.; Johnson, Karen C.; Hess, Rachel; Gregory, Thomas; Bradley, Catherine S.; et al.
Abstract : Objective: The objective of this study was to examine the strength and direction of the association between urinary symptoms and both poor quality sleep and daytime sleepiness among women with urgency urinary incontinence. Methods: A planned secondary analysis of baseline characteristics of participants in a multicenter, double-blinded, 12-week randomized controlled trial of pharmacologic therapy for urgency-predominant urinary incontinence in ambulatory women self-diagnosed by the 3 Incontinence Questions was performed. Urinary symptoms were assessed by 3-day voiding diaries. Quality of sleep was assessed using the Pittsburgh Sleep Quality Index (PSQI) and daytime sleepiness using the Epworth Sleepiness Scale. Results: Of the 640 participants, mean (SD) age was 56 (±14) years and 68% were white. Participants reported an average of 3.9 (±3.0) urgency incontinence episodes per day and 1.3 (±1.3) episodes of nocturia per night. At baseline, 57% had poor sleep quality (PSQI score, >5) and 17% reported daytime sleepiness (Epworth Sleepiness Scale score, >10). Most women (69%) did not use sleeping medication during the prior month, whereas 13% reported use of sleeping medication 3 or more times per week. An increase in total daily incontinence episodes, total daily urgency incontinence episodes, total daily micturitions, and moderate to severe urge sensations were all associated with higher self-report of poor sleep quality according to the PSQI (all P ⩽ 0.01). Higher scores on the Bother Scale and the Health-Related Quality of Life for overactive bladder on the Overactive Bladder Questionnaire were similarly associated with higher rates of poor sleep quality (both P ⩽ 0.01). In subgroup analysis of those who took sleeping medications less than twice a week, there was still a significant relationship between incontinence measures and quality of sleep as measured by the PSQI. In multivariable analyses, greater frequency of nighttime urgency incontinence was associated with poor sleep quality ( P = 0.03). Conclusions: Among ambulatory women with urgency urinary incontinence, poor sleep quality is common and greater frequency of incontinence is associated with a greater degree of sleep dysfunction. Women seeking urgency urinary incontinence treatment should be queried about their sleeping habits so that they can be offered appropriate interventions. Abstract : There is a high prevalence of poor sleep quality among ambulatory women with urgency urinary incontinence, and greater frequency of incontinence is associated with a greater degree of sleep dysfunction.